1977
DOI: 10.1177/030098587701400110
|View full text |Cite
|
Sign up to set email alerts
|

Feline Panleukopenia I. Pathogenesis in Germfree and Specific Pathogen-Free Cats

Abstract: A bst ract. Ge rmfree a nd spe cific pathogen -fr ee cats we re inocul at ed wit h panleukopen ia viru s . Tot al leu cocyte co unts de creased signific antl y in both ger mfree a nd spec ific path ogen -fr ee cats. Clinical illness was not see n in a ny gc rmfree ca t. Spec ific pa thoge n-free ca ts had an or exi a and slight diarrhea 5-6 day s afte r ino cul ati on . No ne of the ca ts died . Both ge rmfree a nd spec ific pathogen -fr ee cat s had th ymi c involuti on . No o the r g ross lesions were see n.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
2

Year Published

1980
1980
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 4 publications
(3 reference statements)
3
22
0
2
Order By: Relevance
“…Experimental infection of specific pathogen-free (SPF) or germfree cats with FPLV generally leads to mild diseases ( 23 , 24 ). No or slight intestinal lesions can be observed in infected germfree cats ( 23 ), which suggests that the intestinal lesions are caused by secondary bacterial, rather than primary viral, infection.…”
Section: Clinical Features Of Fplv and Cpv In Their Original Hostsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental infection of specific pathogen-free (SPF) or germfree cats with FPLV generally leads to mild diseases ( 23 , 24 ). No or slight intestinal lesions can be observed in infected germfree cats ( 23 ), which suggests that the intestinal lesions are caused by secondary bacterial, rather than primary viral, infection.…”
Section: Clinical Features Of Fplv and Cpv In Their Original Hostsmentioning
confidence: 99%
“…Note, however, that the experimental infection of SPF cats with FPLV generally leads to mild disease ( 23 , 24 ). In this regard, the study reported by Goto et al ( 31 ) is intriguing.…”
Section: Virulence Of Cpv-2a and -2b In Catsmentioning
confidence: 99%
“…Essas lesões são caracterizadas por necrose tecidual, atrofia e fusão de vilosidades intestinais e rarefação tecidual hematopoiética (Csiza et al 1971, Carlson et al 1977. Elas evidenciam o tropismo do parvovírus por células com elevada taxa de mitose e seu efeito citopático (Parrish 1995).…”
Section: Discussionunclassified
“…A panleucopenia felina é conhecida desde 1920 como uma importante doença contagiosa de felinos domésticos e selvagens (Carlson et al 1977 da panleucopenia felina (VPF) e parvovírus canino (CPV) (Garcia et al 2011, Battilani et al 2013, pertencentes à Família Parvoviridae. São vírus pequenos, não envelopados, com uma fita simples de DNA e extremamente resistentes no ambiente e a desinfetantes (Greene & Addie 2006).…”
Section: Introductionunclassified
“…The basis of these clinical manifestations is cytolytic replication of the infecting parvovirus in cells of the cryptal epithelium of the intestine [89][90][91]. Giving similar effects are nutritional stress conveyed by starving or change in diet and, last but not least, bacterial or parasitic superinfections [94][95][96]. For instance, cell proliferation in the intestine of suckling dogs is usually low and so is the incidence of severe enteritis [92,93].…”
Section: Parvoviruses As Pathogensmentioning
confidence: 99%